Allergens of Regional Importance in Korea - Jeong, Kyoung Yong; Park, Jung-Won (Frontiers in Allergy, 2021)
Allergen repertoire should reflect the region's climate, flora, and dining culture to allow for a better diagnosis. In Korea, tree pollens of oak and birch in the spring in conjunction with weed pollens of mugwort, ragweed, and Japanese hop are the main causes of seasonal allergic rhinitis. More specifically, the sawtooth oak in Korea and the Japanese hop in East Asia make a difference from western countries. Among food allergens, the sensitization to silkworm pupa and buckwheat is also common in Korean patients. Honey bee venom due to apitherapy in traditional medicine and Asian needle ant, Pachycondyla chinensis, are important causes of anaphylaxis in Korea. Climate change, frequent overseas traveling, and international product exchanges make situations more complicated. Ragweed, for example, was not native to Korea, but invaded the country in the early 1950s. Recently, Japanese hop and Asian needle ants have been recognized as important invasive ecosystem disturbing species in western countries. However, the molecular properties of the component allergens from these unique culprit allergens have been poorly characterized. The present review summarizes the molecular studies on the allergens of regional importance in Korea.